Kajian awal laju reaksi fotosintesis untuk penyerapan gas CO2 menggunakan mikroalga Tetraselmis chuii - Elida Purba; Ade Citra Khairunisa (Jurnal Rekayasa Proses, 2012)
The background of the present study was the facts that the increase of carbon dioxides concentration in the air due to industrial activities and fossil fuel combustion certainly leads to global warming. In order to reduce carbon dioxides concentration, photosynthesis reaction using Tetraselmis chuii was one of the potential methods to use. The present study aimed at determining the rate constant of reaction that used Tetraselmis chuii. The study was carried out by firstly saturating sea water as a culture media with carbon dioxide in order to reduce the influence of carbon dioxide diffusion through the media. Microalgae were then put inside the photo-bioreactor at different operating conditions. The operating variables investigated in the present work were temperature (28C, 30C and 35C) and inlet CO2 gas concentration (4, 9 and 14%) with a complete random experimental design. Experimental results showed that the highest absorption capacity was achieved at 30C and 35C for each inlet CO2 concentration. However, the order of reaction with respect to CO2 concentration could not have been determined since the correction factors (R) values obtained from graphical analysis of first, second and third order reactions were not significantly different.